2009
DOI: 10.1111/j.1477-2574.2009.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy is associated with an improvement in survival in patients with irresectable hilar cholangiocarcinoma

Abstract: This prospective clinical cohort study has demonstrated that radical surgery and palliative Photofrin-PDT are associated with an increased survival in patients with hilar cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…In contrast, the cure rates for nasopharyngeal carcinoma [5] and superficial recurrent urothelial carcinoma HCl [6, 7] are suboptimal with respect to PDT and warrant improvement. Moreover, non-resectable perihilar cholangiocarcinomas respond better to PDT than to any other last-line treatment such as chemotherapy [8], but all available treatments (including PDT) are currently palliative and not curative. The recalcitrant nature of these tumor types to PDT is believed to stem from the use of photosensitizers with suboptimal spectral properties and poor pharmacokinetics as well as the activation of cell survival pathways by tumor cells following PDT [2, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the cure rates for nasopharyngeal carcinoma [5] and superficial recurrent urothelial carcinoma HCl [6, 7] are suboptimal with respect to PDT and warrant improvement. Moreover, non-resectable perihilar cholangiocarcinomas respond better to PDT than to any other last-line treatment such as chemotherapy [8], but all available treatments (including PDT) are currently palliative and not curative. The recalcitrant nature of these tumor types to PDT is believed to stem from the use of photosensitizers with suboptimal spectral properties and poor pharmacokinetics as well as the activation of cell survival pathways by tumor cells following PDT [2, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, including two randomized clinical trials, have found that PDT is superior to biliary stenting alone in the treatment of unresectable cholangiocarcinoma, improving both survival as well as quality of life 2,3,8-13. Additionally, it was recently shown that survival in patients who underwent PDT was similar to those in whom curative surgery was attempted but who had positive resection margins, despite the fact that the PDT group had more advanced clinical T stages 14…”
Section: Discussionmentioning
confidence: 99%
“…При активации препарата образуются свободные радика-лы кислорода, приводящие к повреждению окружающих клеток опухоли. В ряде исследований было показано, что медиана выживаемости при ФДТ как неоадъювантного метода терапии составила от 330 до 493 дней после поста-новки диагноза и однолетняя выживаемость -от 45 до 83% [20,24].…”
Section: хирургия 4 2015unclassified